Supporting international medical graduates' transition to their host‐country: realist synthesis. Issue 10 (15th September 2016) - Kehoe, Amelia; McLachlan, John; Metcalf, Jane; Forrest, Simon; Carter, Madeline; Illing, Jan
Abstract : Context: Many health services and systems rely on the contribution of international medical graduates (IMGs) to the workforce. However, concern has grown around their regulation and professional practice. There is a need, in the absence of strong evidence and a robust theoretical base, for a deeper understanding of the efficacy of interventions used to support IMGs' transition to their host countries. This study seeks to explore and synthesise evidence relating to interventions developed for IMGs. It aims to provide educators and policy makers with an understanding of how interventions should be developed to support IMGs in their transition to the workplace, particularly looking to identify how and why they are effective. Methods: The realist synthesis involved an initial systematic search of the literature for the period January 1990 to April 2015. Secondary searches were conducted throughout the review in order to inform and test the developing programme theory. The context, mechanism and outcome data were extracted from all sources meeting the inclusion criteria. Fourteen case studies were included to further aid theory refinement. Results: Sixty‐two articles were identified, describing diverse interventions of varying intensity. A further 26 articles were identified through a secondary search. The findings illustrate that, alongside a developed programme, ongoing support and cultural awareness at organisational and training levels are crucial. Individual differences must also be taken into consideration. This will ensure that IMGs engage in transformative learning, increase their levels of self‐efficacy and cultural health capital, and reduce feelings of stress and anxiety. These factors will have an impact on work, interactions and cultural adjustment. Conclusions: Organisational, training and individual contexts all play a role in IMGs' adjustment during the transition process. Establishing ongoing support is critical. A list of recommendations for implementation is given. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss